Curving the social, or, why antagonistic rituals in Brazil are variations on a theme. (11th December 2015) - Shapiro, Matan
Abstract : What can we learn about religious diversity in Brazil if we isolate ritual practices from their sociocultural surround? Using vocabulary developed by Don Handelman in his framework of 'ritual in its own right', I discuss this question in the context of low‐income Northeast Brazil. I demonstrate that Afro‐Brazilian possession rites and Christian‐Evangelical prayers ( oração ) transform the lives of the persons who practise them in ways that are intrinsic to their self‐organization, internal complexity, and differentiating 'curves'. I consequently argue that these rites are not representations of antagonistic moral prescriptions for good living but rather variations on a single theme of sociality.